Risk of leukemia in first degree relatives of patients with nonsyndromic cleft lip and palate - Eduardo GONÇALVES; Daniella Reis Barbosa MARTELLI; Ricardo Della COLETTA; Alexandre Rezende VIEIRA; Antônio Prates CALDEIRA; Hercílio MARTELLI JÚNIOR (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The aim of this study was to determine the frequency of leukemia in parents of patients with nonsyndromic cleft lip and/or cleft palate (NSCL/P). This case-control study evaluated first-degree family members of 358 patients with NSCL/P and 1,432 subjects without craniofacial alterations or syndromes. Statistical analysis was carried out using Fisher's test. From the 358 subjects with NSCL/P, 3 first-degree parents had history of leukemia, while 2 out of 1,432 subjects from the unaffected group had a family history of leukemia. The frequency of positive family history of leukemia was not significantly increased in first-degree relatives of patients with NSCL/P.